Strengthening the Capacity of Kaliyoso Village MSMEs through E-Commerce Optimization and PIRT Product Legality - Meiriyanti, Rita; Nastiti, Prianka Ratri; Fathurachman, Chadyan; Kurniawan, Bayu (Yayasan Ahmar Cendekia Indonesia, 2025)
MSMEs in Kaliyoso Village, Kangkung Subdistrict, Kendal Regency face obstacles in digital marketing and product legality. Many businesses do not have the skills to use e-commerce platforms and do not have PIRT, making it difficult to expand the market. This service program aims to increase the capacity of MSMEs through training in creating online stores on Shopee and technical assistance for PIRT registration. Activities are carried out with a participatory approach through the stages of socialization, technical training, and assistance to MSME actors. The training focused on hands-on practice of using Shopee and PIRT registration procedures according to the provisions of the Health Office. The results of the activities showed an increase in participants' skills in marketing products digitally and a better understanding of the importance of product legality. This program not only encourages the independence of MSME players in developing their businesses, but also triggers the formation of a digital MSME community as an effort to sustain local economic empowerment.